An educational programme to facilitate critical thinking within the nursing perspective - Pretoruis, Louise; Van Dyk, Agenes; Small, Luis; Amukugo, Hans Justus (International Journal of Advanced Nursing Studies, 2016)
This article is focuses on an educational programme to facilitate critical thinking within the nursing perspective. For the purpose of developing an educational programme; the study was conducted in four phases, beginning with a needs assessment in Phase 1 through which the researcher determined the need of student nurses in terms of critical thinking. The deductive data analysis of phase 1 served as conceptual framework for the development of education programme in phase 2.Phase 2 consisted of the development of educational framework to facilitate critical thinking in student nurses. Specific educational approaches and a philosophical framework were employed during the development of the programme. An expert opinion on the programme was obtained before the implementation could be concluded in phase 3. Phase 3 and 3 of the study were conducted simultaneously. Phase 3 covered the implementation of the educational programme and Phase 4 the evaluation.The process itself includes, the purpose of the development of the programme, conducting a situational analysis; utilization of philosophical approaches, developing the educational programme; content of the programme; educational and curriculum approaches integrated into the development of an educational programme and strategies to overcome obstacles during the implementation of an educational programme.